2017
DOI: 10.1038/s41598-017-07152-5
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of recombinant Mayaro virus strains from the Amazon basin

Abstract: Mayaro virus (MAYV), causative agent of Mayaro Fever, is an arbovirus transmitted by Haemagogus mosquitoes. Despite recent attention due to the identification of several cases in South and Central America and the Caribbean, limited information on MAYV evolution and epidemiology exists and represents a barrier to prevention of further spread. We present a thorough spatiotemporal evolutionary study of MAYV full-genome sequences collected over the last sixty years within South America and Haiti, revealing recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 62 publications
(93 reference statements)
3
79
0
2
Order By: Relevance
“…The global expansion of CHIKV due to a single point mutation ( 30 ) has previously demonstrated that the adaptation of an arbovirus to a new vector species can be devastating. The adaptation of MAYV to the Aedes vector has been analyzed ( 31 ), and the emergence of hybrid genotypes D and L suggests that Aedes mosquitoes can play an important role in the urban diffusion of MAYV. Ae.…”
Section: Discussionmentioning
confidence: 99%
“…The global expansion of CHIKV due to a single point mutation ( 30 ) has previously demonstrated that the adaptation of an arbovirus to a new vector species can be devastating. The adaptation of MAYV to the Aedes vector has been analyzed ( 31 ), and the emergence of hybrid genotypes D and L suggests that Aedes mosquitoes can play an important role in the urban diffusion of MAYV. Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Inferences that are based only on clinical-epidemiological notifications are complicated by underreporting of cases by the national reporting system [16], mostly due to the co-circulation and co-infection with viruses that cause overlapping symptoms, such as Zika and dengue viruses [17-19]. Moreover, CHIKV serological tests may cross-react with other alphaviruses, such as Mayaro virus, that circulate in the north and centre-west regions of Brazil [20, 21]. In this context, it is challenging to use only clinical-epidemiological and serological data to evaluate the true extent of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…While the origin of this virus strain remains unknown, numerous scenarios have been proposed 1,16,17 . Recombination is an important factor driving viral diversity 18,19 , and has been reported as a possible mechanism favoring cross-species transmission of CoV and increasing its adaptability to a new host 20,21 . Recombination was a critical factor in the emergence of Middle East respiratory syndrome coronavirus (MERS-CoV) in 2012 from bat reservoirs 22,23 .…”
Section: Mainmentioning
confidence: 99%